Gap Analysis of Promotional Strategies for Express Logistics Operations in Indonesia: A Case Study on JNE Logistics - RAJAVADIVEL SANTHANAKRISHNAN; CHIRAG NAITHANI; BHANUPRIYA PARASAR; WENNY GILLIANI (AIBPM Publisher, 2019)
Indonesian logistics sector is poised for expeditious growth over the coming years fueled by the burgeoning economy, expanding middle class urban population, robust manufacturing sector, and large domestic consumption. Although challenges such as poor infrastructure, centralized port network, protracted and bureaucratic customs procedures, extortionate transportation costs, complex regulatory environment, plummeting commodity prices, limited access to banking system, and geotechnical challenges of the archipelagic state exist, the demand for modern warehousing and logistics facilities in Indonesia is proliferating as businesses have realized the positive impact of improved logistics efficiencies on their financial statements. Further, the fledging Indonesian logistics sector – boosted by increased government spending on infrastructure development since 2015 – has unambiguous indications of an imbalance in demand and supply of efficacious warehousing space thus presenting a plethora of opportunities for domestic entrants and international incumbents alike. However, local incumbents such as JNE Logistics, whose inception in 1990 marked their entry in an uncontested blue ocean market, is now battling in a red ocean to keep their stewardship afloat. This paper is a feasibility study of JNE’s marketing activities evaluating the gaps in their current go-to-market blueprint for their express logistics operations and recommending innovative promotional strategies which is not easily imitable. Keywords: express logistics, warehousing, strategy, marketing, Indonesia.